A database and synthesis of northern peatland soil properties and Holocene carbon and nitrogen accumulation. (September 2014) - Loisel, Julie; Yu, Zicheng; Beilman, David W; Camill, Philip; Alm, Jukka; Amesbury, Matthew J; Anderson, David; Andersson, Sofia; Bochicchio, Christopher; Barber, Keith; Belyea, Lisa R; Bunbury, Joan; et al.
Here, we present results from the most comprehensive compilation of Holocene peat soil properties with associated carbon and nitrogen accumulation rates for northern peatlands. Our database consists of 268 peat cores from 215 sites located north of 45°N. It encompasses regions within which peat carbon data have only recently become available, such as the West Siberia Lowlands, the Hudson Bay Lowlands, Kamchatka in Far East Russia, and the Tibetan Plateau. For all northern peatlands, carbon content in organic matter was estimated at 42 ± 3% (standard deviation) for Sphagnum peat, 51 ± 2% for non- Sphagnum peat, and at 49 ± 2% overall. Dry bulk density averaged 0.12 ± 0.07 g/cm 3, organic matter bulk density averaged 0.11 ± 0.05 g/cm 3, and total carbon content in peat averaged 47 ± 6%. In general, large differences were found between Sphagnum and non- Sphagnum peat types in terms of peat properties. Time-weighted peat carbon accumulation rates averaged 23 ± 2 (standard error of mean) g C/m 2 /yr during the Holocene on the basis of 151 peat cores from 127 sites, with the highest rates of carbon accumulation (25–28 g C/m 2 /yr) recorded during the early Holocene when the climate was warmer than the present. Furthermore, we estimate the northern peatland carbon and nitrogen pools at 436 and 10 gigatons, respectively. The database is publicly available athttps://peatlands.lehigh.edu .